1991
DOI: 10.3109/01480549109017876
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Subchronic Aflatoxin Exposure on Growth and Progression of Ehrlich's Ascites Tumor in Mice

Abstract: The present investigation was undertaken to assess whether aflatoxin B1 (AFB1) has any modulatory effect on the growth and progression of Ehrlich's ascites tumor (EAT) in mice or not. Male Swiss albino mice were treated with 0, 70, 350 and 700 micrograms AFB1/kg body weight in 0.2 ml corn oil on alternate days, orally, for two weeks. Treated animals were challenged with 1 x 10(6) cells of Ehrlich's ascites tumor. Animals were monitored for the appearance of palpable tumor, body weight gain as a measure of tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Cunningham chambers were prepared using a glass slide, coverslips and doubled-sided tape. The chambers were loaded with a known volume of assay mixture, sealed with xylene and incubated at 37°C for 1 h. The plaques were counted under a light microscope and expressed as PFC per 10 6 spleen cells [8].…”
Section: Pfc Assaymentioning
confidence: 99%
“…Cunningham chambers were prepared using a glass slide, coverslips and doubled-sided tape. The chambers were loaded with a known volume of assay mixture, sealed with xylene and incubated at 37°C for 1 h. The plaques were counted under a light microscope and expressed as PFC per 10 6 spleen cells [8].…”
Section: Pfc Assaymentioning
confidence: 99%
“…Our studies have shown that aflatoxin has a profound immunosuppressive effect in growing animals (9,10). The macrophage defence mechanism and cell mediated immunity have been found to be very sensitive to aflatoxin toxicity in growing animals (9)(10)(11).…”
Section: Introductionmentioning
confidence: 93%
“…The prevailing conditions of malnourishment may also aggravate the toxic and carcinogenic potentials of aflatoxin in a developing host (34,35). Our earlier observations have already shown that aflatoxin may enhance susceptibility of a host towards tumor challenge (11). A developing host under such circumstances may not only be deficient in metabolizing and disposing of several xenobiotics, but also be susceptible to various types of infections and malignancies due to the immunosuppressive effects of aflatoxin (9,11).…”
Section: Effects Of Afb1 On Biotransformation Enzymesmentioning
confidence: 99%
“…Plaque forming cell (PFC) assay A previously described method (Raisuddin et al 1991) was followed with slight modifications to perform the PFC assay. Briefly, 24 Swiss albino mice were divided into 4 groups (n = 6).…”
Section: Maintenance Of Animalsmentioning
confidence: 99%